Le processus d’observation, son développement et ses effets dans la méthode des autoconfrontations croisées en clinique de l’activité - Antoine Bonnemain; Emilie Perrot; Katia Kostulski (Activités)
The purpose of this article is to analyze the development of observation as an activity within the crossed self-confrontation method. The first part describes the theoretical connections between observation and intersubjectivity in the observation process, and the psychological process that is involved. The second part presents an intervention based on the crossed self-confrontation in activity clinic. In this example, we analyze the effects of the observation process as it is perfomed among workers. We then study the migration of intersubjectivity in the observation process and its effects on the way that professionals might think about their work. More particularly, we suggest that observation leads professionals to “segment” their work activity, and thus to construct new objects of thought about work activity, through activity observation and analysis.